Adolescent quality of life: A school-based cohort study in Western Australia. - Meuleners, L.; Lee, Andy (Japan Pediatric Society (John Wiley & Sons), 2003)
Background: Quality of life (QOL) has received increasing attention in pediatrics medicine recently. Improving QOL is the primary justification for many interventions, medications and therapies. The present study is a school-based longitudinal study which aims to investigate the factors affecting QOL of adolescents in Western Australia over a 6-month period. Methods: A generic self-reported questionnaire was administered twice to participants from 20 schools in Perth at 6 months apart. In addition to QOL scores and physical health status, demographic and other information was also collected. For the cohort of 363 students who participated in the initial survey, 300 of them completed the second questionnaire.Results: A significant change in QOL score between baseline and 6 months was observed. Results from fitting a hierarchical mixed regression model indicated that 55% of the variation in QOL was due to differences between individuals, and was significantly associated with age, control, opportunities and perceptions of physical health, while the remaining variance component could be attributed to within-individual changes. Improved control and opportunities appeared to have a significant positive impact on QOL, whereas increasing age and deterioration in physical health had the opposite effect. Conclusions: The hierarchical regression analysis has enabled valid inferences to be made based on the observed longitudinal data. Perceptions of physical health, age, control and opportunities available are related to adolescent QOL. The findings have implications on evidence-based practices and childhood health issues.